Profile of Cardiorespiratory Fitness, Flexibility and Fat Percentage of Junior High School Students in Jatinangor - Akbar, Gemuruh Putra; Purba, Ambrosius; Suhadi, Yenni Zuhairini (Althea Medical Journal, 2017)
Background: Obesity and physical inactivity is a major risk factor for non-communicable disease and global mortality in adolescent. Lack of physical activity will lead the condition into poor physical fitness, measured by cardio respiratory fitness (maximum oxygen volume, VO2 max), and other components such as flexibility. The study aimed to describe VO2 max, flexibility and fat percentage among junior high school students in Jatinangor.Methods: The study was a descriptive observational study using descriptive analysis.Â  VO2 max was assessed using Astrand Ryhming step test, flexibility was measured using flexometer sit and reach test, and fat percentage was determined using bioelectrical impedance analysis scale. The subjects were junior high school students who were study in 1st, 2nd and 3rd grade in Jatinangor Junior High School based on stratification sampling method. It was conducted from SeptemberâOctober 2013.Results: Total subjects were 110 students consisted of male (n=52) and female (n=58).Â  The VO2 max were in good and above category, 57.69% of male (50.37 Â± 9.80 ml/kg/min), and 60.34% of female (37.66Â±7.03 ml/kg/min). The flexibility for both males and females were within excellent category (67.31%, 26.56 Â±7.14 cm and 67.24%, 27.29Â±6.64 cm respectively). The fat percentage in females were within healthy category (67.24%, 25.28 Â± 6.85 %), meanwhile male were within underfat category (48.08%, 11.66 Â± 5.83 %).Conclusions: The majority of VO2 max, and flexibility both in male and female were good. The fat percentages were good in female students, while in male students were under normal range.DOI:Â 10.15850/amj.v4n2.1085